1999
DOI: 10.1002/(sici)1522-9505(19991201)272:1<65::aid-apmc65>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics of lignin/polypropylene composites suitable for industrial applications

Abstract: Lignin/polypropylene composites were compounded by melt blending in a thermokinetic mixer and then ASTM specimens suitable for tensile testing were made by injection moulding. Two polypropylenes with different molecular weights were used as matrices. Lignin contents in the composites ranged from 10 to 55 wt.‐%. Tensile modulus, strength and elongation were determined for those composites. The experimental data thus obtained were thus mathematically fitted to several micromechanical models. Micromechanical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Apart from cellulose, lignin present in lignocellulosic plants contains aromatic rings and UV‐absorbing functional groups . Lignin possesses excellent antioxidant properties, which makes it suitable for enhancing the thermal and oxidation stability of polymers in blends . Lignin is a branched phenolic polymer that is not compatible with carbohydrate polymers, such as cellulose, and requires a covalent interaction for composite formation.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from cellulose, lignin present in lignocellulosic plants contains aromatic rings and UV‐absorbing functional groups . Lignin possesses excellent antioxidant properties, which makes it suitable for enhancing the thermal and oxidation stability of polymers in blends . Lignin is a branched phenolic polymer that is not compatible with carbohydrate polymers, such as cellulose, and requires a covalent interaction for composite formation.…”
Section: Introductionmentioning
confidence: 99%
“…When modified lignin is incorporated into a PP matrix, the overall physical properties of the resulting composite are improved, such as when clay or talc is integrated into a general PP composite. Table 5 shows that the tensile properties of the PP/THFL blended matrix slightly decreased with the THFL content compared to the PP/lignin blend [5,6,7]. There was no significant change in the tensile strength, although the tensile strength of the matrix containing 50% THFL was slightly lower than that of the matrix containing 25% THFL.…”
Section: Resultsmentioning
confidence: 99%
“…However, the elongation of such materials tends to decrease dramatically with increasing lignin content in fact, the physical properties of thermoplastic blends are significantly degraded when more than 10%~25% of lignin is incorporated into synthetic polymers, as shown in Figure 1 [5,6,7,8]. Therefore, maximizing the amount of lignin in thermoplastic materials while minimizing the corresponding degradation of mechanical properties is a very important research topic.…”
Section: Introductionmentioning
confidence: 99%
“…Gonzales-Sánchez and Espósito Alvarez [58] found that the incorporation of KRL (10-55 wt%) into polypropylene was accompanied by an increase in tensile modulus with lignin content and a decrease in maximum tensile strength, indicating poor adhesion between the nonpolar structure of PP and more polar structure of lignin and a poor dispersion into the matrix. Gonzales-Sánchez and Espósito Alvarez [58] found that the incorporation of KRL (10-55 wt%) into polypropylene was accompanied by an increase in tensile modulus with lignin content and a decrease in maximum tensile strength, indicating poor adhesion between the nonpolar structure of PP and more polar structure of lignin and a poor dispersion into the matrix.…”
Section: Lignin In Thermoplastic Compositesmentioning
confidence: 99%